Chondromyxoid fibroma of rib with a novel chromosomal translocation: a report of four additional cases at unusual sites - Parwani Anil V; Surti Urvashi; Gollin Susanne M; Goodman Mark A; McGough Richard L; Armah Henry B; Rao Uma NM (BMC, 2007)
Abstract Background Chondromyxoid fibromas (CMFs) are rare benign chondroid/myxoid matrix-producing tumors that occur in metaphyses of long tubular bones, and very rarely in small bones of hands and feet. Flat bone involvement is even more uncommon. Prior cytogenetic analyses have identified complex abnormalities involving chromosome 6 in the majority of cases. Methods A search for CMF over an 8-year period (1999-2006) from the surgical pathology files of our institution yielded 16 cases. Four cases occurred in relatively unusual regions, three from the small bones of distal extremities and one from the rib. The rib lesion wassubmitted forroutinecytogenetic analysis. Results Radiographic studies revealed that all four lesions were well-defined expansile radiolucent lesions which expanded the bony cortices with lobulated margins, sclerotic rim, septation, and no calcification. Morphologically, all four lesions showed typical features of CMF and had low proliferative index with Ki-67. Cytogenetic analysis on the rib lesion revealed a novel chromosomal translocation, t(1;5)(p13;p13). None of the four patients had a recurrence after a mean duration of follow-up of 24 months. Conclusion CMF originating in unusual locations should be distinguished from chondrosarcomas, especially on small biopsies, and should be included in the differential diagnosis. As previously noted in the literature, the cells can be positive for actin but unlike conventional chondroid neoplasms can be negative for S-100. To our knowledge, this is the first report describing a novel chromosomal translocation, t(1;5)(p13;p13) in CMF.